Applying Polarimetric Target Decomposition to 2D Turntable ISAR Imagery of a Complex Vehicle. (19th July 2022) - Demirci, Sevket
Abstract : The capabilities of polarimetric target decomposition in SAR-based ATR applications are investigated by using 2D turntable ISAR imagery of a T-72 tank. To characterize target's anisotropic scattering properties, wide-angle case is considered through the employment of a distinct polarimetric analysis procedure based on angular averaging of the covariance matrix. The results of the application of the three types of coherent decomposition, that is, Pauli, Krogager, and Cameron decomposition, and one incoherent decomposition, that is, eigenvector/eigenvalue decomposition, are analyzed and compared in terms of the identification of the physical scattering mechanisms. The usefulness of the various secondary parameters, including orientation, symmetry, and entropy, is also discussed. It is found that Pauli and Krogager decomposition can be readily applied for quick discrimination between the odd- and even-bounce reflectors. For a more detailed description of scattering mechanisms, either the Cameron or eigenvector/eigenvalue decomposition can be employed since their classification images are shown to be mostly consistent with each other. The results demonstrate that the decomposition features can be effectively utilized in subsequent ATR processes.